Editor’s note - Momčilović, Ana (Medical Word, 2024)
Dear colleagues, The latest, quite interesting and meaningful issue of the journal “Medical Word” is in front of you, with various topics, providing readers with the opportunity to improve and upgrade special professional knowledge, but also to compare it with their own experiences and work results. At the beginning of this issue of the journal, a group of authors from the Republic of North Macedonia presented the results and analysis of a survey on oral health that was conducted among primary healthcare workers in North Macedonia, as well as students of dentistry and medicine. The role of essential oils in the fight against infections of the respiratory system and their antimicrobial effect was presented by a group of authors who dealt with this problem from different aspects, showing the importance of interdisciplinary cooperation in the treatment of pediatric patients. The problem of abuse and neglect of children, as well as the resulting injuries, is increasing, so the authors of a paper have just presented the results of the treatment of abused children, with a special emphasis on prevention measures and on everything that we as a society can do to prevent violence against children. In this issue of the journal, a comprehensive and illustrative X-ray presentation of craniosynostosis, as well as a presentation of a case of hydrocephalus in practice, is also given. In the end, as always, there is a documented and thorough work from the history of medicine. Therefore, continuing our established conception of the journal, and following our broad thematic orientation, we present six new papers, which are available to readers in open access, as before. And this time, we invite our respected colleagues to send their papers to our journal. We are impatiently waiting for your papers. Editor-in-Chief Prim. Ana Momčilović, MD, PhD, Professor of vocational studies